Arte Aqui é Mato. (Cuiaba : Museu de Arte e de Cultura Popular, 1990)
de Aguiar, Jared Moreira ; de Barros, Dalva Maria ; Barros, Jonas Ferreira ; Cortez, Benedito aleixo ; de Costa, Joao Sebastiao Francisco ; Grosso, Mato ; Pino, Wlademir Dias ; Espindola, Humberto ; Fonteles, José Benedito ; Friedlander, Mario ; Guimaraes, Sergio Henrique ; Irigaray, Clovis Hugueney ; Lopes, Carlos ; Maldonado, Joao Mario da Silva ; de Mello, José Mauricio Marinho ; Mickosz, Marisa Deliberador ; Miglacio, Caia ; Moura, Clinio ; Nunes, Benedito Luis ; de Oliveira, Julio Cesar ; de Paula, Gervane Ferreira ; Penna, Regina ; Costa, Nilson Pimenta da ; Pinto, Adao Dominiciano ; Santos, Alcides Pereira dos ; Santos, Marcio Aurelio dos ; Santos, Osvaldina dos ; Silva, Dirce Nestor da ; Silva, Jadir Antonio da ; Silva, Joana Maria Da ; Silva, Sebastiano ; de Souza, Adir Sodré ; Sucksdorff, Arne ; Silva, Marcelo Velasco e ; Vitart, Maty
biografie
boek